Land-walking vs. water-walking interventions in older adults: Effects on aerobic fitness - Andrew Haynes; Louise H. Naylor; Howard H. Carter; Angela L. Spence; Elisa Robey; Kay L. Cox; Barbara A. Maslen; Nicola T. Lautenschlager; Nicola D. Ridgers; Daniel J. Green (Elsevier, 2020)
Background: Low cardiorespiratory fitness is an independent predictor of all-cause and cardiovascular mortality, and interventions that increase fitness reduce risk. Water-walking decreases musculoskeletal impact and risk of falls in older individuals, but it is unclear whether water-walking improves aerobic fitness in the same way as weight-dependent land-walking. This randomized controlled trial involved 3 intervention groups-a no-exercise control group (CG), a land-walking (LW) group, and a water-walking (WW) group-to investigate the comparative impacts of LW and WW to CG on fitness. Methods: Both exercise groups attended individually tailored, center-based, intensity-matched 3 × weekly sessions for 24 weeks, which progressed to 150 min of exercise per week. This was followed by a 24-week no-intervention period. Maximal graded exercise tests were performed on a treadmill at Weeks 0, 24, and 48. Results: Maximal oxygen uptake increased from Week 0 to Week 24 in both exercise groups (0.57 ± 0.62 mL/kg/min, 0.03 ± 0.04 L/min for LW; 0.93 ± 0.75 mL/kg/min, 0.06 ± 0.06 L/min for WW, mean ± SE) compared to the CG (-1.75 ± 0.78 mL/kg/min, -0.16 ± 0.05 L/min) (group × time, p < 0.05). Time to exhaustion increased significantly following LW only (123.4 ± 25.5 s), which was significantly greater (p = 0.001) than the CG (24.3 ± 18.5 s). By Week 48, the training-induced adaptations in the exercise groups returned to near baseline levels. Conclusion: Our study supports current physical-activity recommendations that 150 min/week of moderate-intensity exercise produces improvements in fitness in previously sedentary older individuals. Also, LW and WW elicit similar improvements in fitness if conducted at the same relative intensities. Exercise-naïve older individuals can benefit from the lower impact forces and decreased risk of falls associated with WW without compromising improvements in cardiorespiratory fitness.